Cerebrospinal fluid β-amyloid 42 and tau proteins as biomarkers of Alzheimer-type pathologic changes in the brain - Tapiola, T; Alafuzoff, I; Herukka, S; Parkkinen, L; Hartikainen, P; Soininen, H; Pirttilä, T (American Medical Association, 2009)
Background: There is a clear need to develop an objective diagnostic test for Alzheimer disease (AD). Changes in the levels of cerebrospinal fluid (CSF) tau protein and β-amyloid 42 (Aβ42) peptide in patients with AD have been well documented, but the relationship between these biomarkers and neuropathologic changes in the brain is not established. Objective: To study the relationship between antemortem CSF biomarker levels and Alzheimer-type neuropathologic changes in the brain. Design: Cross-sectional study to correlate levels of CSF Aβ42, total tau, and phosphorylated tau protein with neuropathologic changes in the brain. Setting: Academic research. Patients: The study included 123 patients (79 with clinically diagnosed AD, 29 with other dementia, and 15 with other neurologic disease). All underwent clinical evaluation and provided antemortem lumbar CSF samples, and neuropathologic data were collected from September 11, 1990, to March 13, 2003, in the Department of Neuroscience and Neurology, University of Kuopio, Kuopio, Finland. Main Outcome Measures: Levels of CSF Aβ42, total tau, and phosphorylated tau protein were measured using standard commercial immunoassays. Neuropathologic evaluations included the classic silver impregnation method and immunohistochemistry for Aβ, hyperphosphorylated tau, and α-synuclein. Results: Cerebrospinal fluid Aβ42 and tau protein levels were related to amyloid load and the presence of neurofibrillary pathologic abnormalities in the brain. Cerebrospinal fluid Aβ42 level correlated inversely with total Aβ load in the brain, and CSF tau level correlated with results of immunohistochemistry for hyperphosphorylated tau and with the presence of neocortical neurofibrillary tangles. In multivariate logistic regression analysis, the number of neuritic plaques in the brain remained a significant predictor of decreased CSF Aβ42 level and of increased CSF tau level. Based on the ratio of phosphorylated tau level to Aβ42 level, sensitivity was 91.6%, and specificity was 85.7%, with an overall accuracy of 90.2% for the presence of pathologic neuritic plaque in the brain. Conclusions: Cerebrospinal fluid Aβ42 and tau proteins are biomarkers of AD-associated pathologic changes in the brain. The combination of abnormally low CSF Aβ42 level and abnormally high CSF tau level predicted the presence of AD pathologic features with high accuracy. This combination assay may be helpful in diagnosing the presence of AD pathologic changes in the brain.